Health literacy and risk of viral hepatitis among Chinese school children - Zhang, Dangui; Wen, Darong; He, Ganyuan; Chen, Zhenyu; Zeng, Wenrui; Lu, Lichun; Huang, Chuangfeng; Ba-Thein, William (The Journal of Infection in Developing Countries, 2023)
Introduction: Poor literacy is associated with hepatitis morbidity and mortality. Adolescents are especially at risk of hepatitis C. This study investigated viral hepatitis literacy, risk, and influencing factors among Chinese middle and high school students. Methodology: A supervised self-administered survey was conducted with school children from six schools in Shantou, China. Data on demographics, health literacy, and risk of viral hepatitis were analyzed. Results: A total of 1732 students (from three middle and three high schools) participated in the study. Their major information resources were the internet (39.5%, 685/1732), television (28.8%, 498/1732), family (27.7%, 479/1732), and school (21.2%, 368/1732). The mean literacy score on the manifestations and risk factors of hepatitis was 3.4 ± 2.2 and 4.0 ± 2.3 (out of 8), respectively. Multiple linear regression models showed being female and in high school, having parents with higher education levels, and school or clinicians as an information resource were independent positive predictors, whereas poor awareness of risk factors was a negative predictor for health literacy. Conclusions: We report the risk of hepatitis among Chinese middle and high school students due to limited literacy and poor attitudes towards health-risk behaviors. Health education in school is recommended for preventable health risks among Chinese adolescents.